Affective assemblages matter in socially just pedagogies - Bayat, Abdullah; Mitchell, Veronica (Critical Studies in Teaching and Learning, 2023)
Social justice in higher education is a core concern in South Africa. It involves matters of pedagogy, curriculum, recognition, as well as access to tertiary institutions. In light of the massification of higher education, the question that vexes many educators is how to promote student learning through pedagogical practices that are socially just in themselves and that can also promote social justice. A focus on, and sensitivity to, affect provides a way of addressing this concern. We open up our experiences as educators in different professional fields by using an ethico-onto-epistemological methodology, describing relationships that emerged from our classroom engagements. Affective forces and intensities materialising in our teaching and learning assemblages provide a novel relational approach to enacting social justice. We suggest that an attunement to the affective forces circulating in pedagogical practices has the potential to transform conventional teaching habits thereby promoting socially just teaching.